Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
shortDOI: 10/ggtsmj KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 10/ggtsmj 2339240:DKVPCJ4N 2405685:EBIDU596 2405685:EHX857GT
Keywords: C: Ghana

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
15 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 2339240:4VMARDY3 2405685:S4AUFT59
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

An Atlas of The Forty Colleges of Education in Ghana - Haßler, Björn; Akunor, J. T.; Nyamador, E. S. (2017)
EdTechHub.Source: 2129771:F7ZRYUZX shortDOI: 10/ghgk6m KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911076 10/ghgk6m 2129771:F7ZRYUZX 2129771:U3IVX9WX 2405685:SKFNBK29
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Ghana Reads (Open Learning Exchange Ghana, 2017)
Library Catalog: www.oleghana.org KerkoCite.ItemAlsoKnownAs: 2405685:6EWCFC47

A Survey of ICT Capacity in Ghana's Public Colleges of Education (Transforming Teacher Education and Learning, 2017)
The survey of ICT capacity at 40 colleges of education (CoEs) reflects a considerable amount of work, by many people. The National Council for Tertiary Education (NCTE) acknowledges with thanks, Consumer Insights Consult (CiC) research team, Cyprian Ekor, Elvis Akpabli, Emmanuel Mireku, George Asare, Kennedy Amedume, Daniel Amewuda, Philemon Opoku. NCTE staff, Jacob T. Akunor, Anthony Dzidzornu, Emmanuel Attey Yebuah, Ebenezer Osei Adu, Nicholas Ameyaw and Kwaku Gyampoh. Transforming Teaching and Learning in Ghana (T-TEL) staff, Dr. Björn Haßler, Dr. Rosie Lugg, Mr. Charlie Gordon, Ms. Beryl Opong-Agyei, Dr. Rich Tobin and Ms. Caroline Jordan. Particular thanks is extended to Jacob Tetteh Akunor, who led this exercise on behalf of the NCTE and to the Senior managers, ICT tutors, ICT technicians and student teacher participants at all 40 CoE that participated, and gave so generously of their time and expertise.
EdTechHub.Source: 2129771:CIHUHSF9 shortDOI: 10/ghgk6g KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3930827 10/ghgk6g 2129771:CIHUHSF9 2405685:SX3J7SP9
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode

Unfinished development projects in Ghana: Mechanising collective choice - Williams, Martin (Voxdev, 2017)
Project non-completion, commonly attributed to corruption or clientelism, is in fact often caused by an inability to prioritise public expenditure
KerkoCite.ItemAlsoKnownAs: 2339240:U4IP8MWZ 2405685:A2NZTQ8P 4656463:ZK5ZFFML

OLE Ghana - Open Learning Exchange Ghana (2017)
Library Catalog: www.oleghana.org KerkoCite.ItemAlsoKnownAs: 2405685:A5UVHX67

Ghana Reads - Open Learning Exchange Ghana (2017)
Library Catalog: www.oleghana.org KerkoCite.ItemAlsoKnownAs: 2405685:KKFABZMZ

Fiscal Consolidation to Accelerate Growth and Support Inclusive Development: Ghana Public Expenditure Review - World Bank (World Bank, 2017)
Ghana has experienced an extended period of robust growth since the early 2000s, supported by a favorable external environment and large investment inflows, particularly in the extractive industries. In 2011, as the start of oil production drove a surge in per capita income, Ghana graduated from low-income to lower-middle-income status. Despite the key role of the extractive industries, recent growth has been relatively inclusive, and Ghana achieved its Millennium Development Goal of halving the poverty rate by 2015. However, macroeconomic conditions have deteriorated since 2012, giving rise to substantial domestic and external imbalances. Although external shocks have underscored Ghana's vulnerability to global commodity and financial markets, the recurring nature of its imbalances reflects deeper structural deficiencies in its macroeconomic policies and public financial management (PFM) framework. A heavy focus on commodity exports has accelerated Ghana's recent growth, but the country's economic outlook increasingly hinges on a narrow range of volatile commodity prices.
Accepted: 2017-07-13T17:23:05Z KerkoCite.ItemAlsoKnownAs: 10.1596/27558 2339240:6Y6XC6DS 2405685:WGP4YFMP
Keywords: Agricultural Productivity; Fiscal Policy; Health; Macroeconomic Policy; Pay Reform; Public Education; Public Expenditure; Public Financial Management; Public Wages; Revenue Management; Taxation

Wikipedia:WikiProject Wiki Loves Women/Ghana - Wikipedia (Wikipedia, 2017)
Page Version ID: 766745664 KerkoCite.ItemAlsoKnownAs: 2339240:3T3RZHQT 2405685:7VWJII2A

The Impacts of Fast Track Transformational Teacher Training in Ghana - Wolf, Sharon (Innovations for Poverty Action, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:FALV664A

A Survey of ICT Capacity in Ghana's Public Colleges of Education - Cambridge Education (2017)
EdTechHub.ItemAlsoKnownAs: 2405685:BY4LX4FZ

Centre for National Distance Learning and Open Schooling (CENDLOS) - Editor (COMOSAConnect, 2017)
Centre for National Distance Learning and Open Schooling (CENDLOS) Contact: Joshua C. Mallet, Director Address: C27 Onyasia Crescent, Roman Ridge, PO Box 1627, Castle Osu, Accra, Ghana Phone: 233 3…
Library Catalog: comosaconnect.org EdTechHub.ItemAlsoKnownAs: 2405685:446NUNEW

Ghana Living Standard Survey - GLSS (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:NESIRGQA 2405685:35KGE7PQ
Keywords: Adrenal Medulla; Aging; Animals; Animals; Newborn; Body Weight; Catecholamines; Dopamine beta-Hydroxylase; Epinephrine; Female; Humans; In Vitro Techniques; Maternal-Fetal Exchange; Metaraminol; Morphine; Morphine Dependence; Pregnancy; Rats; Tyrosine 3-Monooxygenase

Fiscal Decentralization in Ghana: Progress and Challenges - Osei, Edna (Institute for Fiscal Studies Ghana, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:86IVWGL2 2405685:PL3W26A4 4656463:HLGC2IQF

Measuring teacher classroom management skills: a comparative analysis of distance trained and conventional trained teachers - Henaku, Christina Bampo; Pobbi, Michael Asamani (Journal of Education and Practice, 2017)
Many researchers and educationist remain skeptical about the effectiveness of distance learning program and have termed it as second to the conventional training method. This perception is largely due to several challenges which exist within the management of distance learning program across the country. The general aim of the study is compare the classroom management skills exhibited by distance trained teachers to that of conventional trained teachers in their field of work. Teacher classroom management was classified into two multidimensional constructs consisting of effective behavior management skills and instructional learning format skills. A quantitative design strategy was adapted for the study. Primary data was collected using a questionnaire from 500 teachers-consisting of 250 conventional and 250 distance trained teachers–and 60 head teachers selected from basic schools across 10 regions in Ghana. Head teachers assessment of teachers served as a means of triangulating results obtained. Data obtained during survey was coded and entered into a SPSS statistical software and subsequently analysed using both descriptive and inferential methods. Results from the study reveal that there were no significant differences in all nineteen (19) items used in measuring teacher classroom control mechanism. Recommendations were made based on the findings of the study.
Publisher: IISTE, No 1 Central, Hong Kong Island, Hong Kong SAR KerkoCite.ItemAlsoKnownAs: 2339240:26FQF7T2 2405685:TZV9EH2V 2405685:XV256FAE 2534378:BN4CL6MA 2534378:V3NGM6FT 2534378:WHV54Y47
Keywords: Behavior Change; Classroom Techniques; Comparative Analysis; Conventional Instruction; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Elementary Education; Elementary School Teachers; Foreign Countries; Ghana; Intermode Differences; Multidimensional Scaling; Questionnaires; Statistical Analysis; Teacher Surveys; Teaching Skills; Training Methods; __:import:01; __:match:final; __:matched; __:study_id:2096069; __finaldtb; ⛔ No DOI found

Involvement of School Management Committees in School-Based Management: Experiences from Two Districts of Ghana. - Abreh, Might K. (Educational Planning, 2017)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:B2J5K7PZ 2405685:4U4JCYGE
Keywords: ⛔ No DOI found

Effectiveness of Interactive Satellite-Transmitted Instruction: Experimental Evidence from Ghanaian Primary Schools. CEPA Working Paper No. 17-08. - Johnston, Jamie; Ksoll, Christopher (Stanford Center for Education Policy Analysis, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:SVCWDI45 2405685:8DZ8SPJV
Keywords: ⛔ No DOI found

National Information Technology Agency (2017)
Library Catalog: nita.gov.gh KerkoCite.ItemAlsoKnownAs: 2405685:DCWIJT8N

Open Schooling: Addressing the Challenge of Out-of-School Youth - Commonwealth of Learning (2017)
Goal 4 of the Sustainable Development Goals aims to ensure inclusive and quality education for all and promote lifelong learning. One target is to ensure that all girls and boys complete free, equitable and quality primary and secondary education by 2030. Yet, this is impossible to achieve within present mainstream education systems. A new way of thinking about schooling is required. // Open Schooling is a model to address this problem without having a disruptive effect on mainstream schooling – a symbiotic relationship, where both systems can benefit from another, is possible. // A multidimensional approach is required. Part of the solution is to improve teaching and learning in conventional schools in order to decrease dropout and increase throughput, while also providing access to quality learning opportunities to out-of-school youth through innovative open schooling. Open schooling
Accepted: 2017-03-28T21:32:23Z Publisher: Commonwealth of Learning (COL) KerkoCite.ItemAlsoKnownAs: 2339240:H7D8S5HN 2405685:NKWVVEW4